1999
DOI: 10.1080/00131919997524
|View full text |Cite
|
Sign up to set email alerts
|

Post-16 English Teaching: From recitation to discussion

Abstract: A BSTR ACTIn an earlier study of the discourse styles of 10 teachers of post-16 E nglish from the northeast of Englan d it was found that teacher-led recitation dominated the classroom discourse thereby imposing linguistic and cognitive constraints on the students. In a follow-up study, four of the teachers were coached in the use of strategies designed to break the recitation script in order to promote wider communicative and more cognitively demandin g options for the students. The ® nding s of the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…It may be, however, as Hardman and Mroz (1999) suggest, that what counts for discussion in many (perhaps most) of postsecondary classrooms is merely recitation as in the case of Guetzkow et al (1954) who described discussion as a place "where students feel free to expose their misconceptions so they can be corrected " (p. 196). Studies employing discussions restricted to very brief exchanges (e.g., Harton et al, 2002;Windschitl, 1999) that limit students' opportunities to extend or develop topics also fail to meet Dillon's criteria for discussion.…”
Section: The Quality Of Discussion In College Classroomsmentioning
confidence: 99%
See 4 more Smart Citations
“…It may be, however, as Hardman and Mroz (1999) suggest, that what counts for discussion in many (perhaps most) of postsecondary classrooms is merely recitation as in the case of Guetzkow et al (1954) who described discussion as a place "where students feel free to expose their misconceptions so they can be corrected " (p. 196). Studies employing discussions restricted to very brief exchanges (e.g., Harton et al, 2002;Windschitl, 1999) that limit students' opportunities to extend or develop topics also fail to meet Dillon's criteria for discussion.…”
Section: The Quality Of Discussion In College Classroomsmentioning
confidence: 99%
“…Similarly, in a study of discussion in a third-year medical course, Foster (1981) found that nearly 75% of student talk during discussions was at the lowest cognitive level while only 2% was at the highest cognitive levels. More recently, in separate studies, Wedman, Smith, and Jared (1994) and Hardman and Mroz (1999) concluded that much of what is taken for discussion in postsecondary classrooms is nothing more than recitation. As Benzing and Christ (1997) observed, it may be that "instructors believe that lecture punctuated by instructor or student questions is a participatory technique" (p 185).…”
Section: The Quality Of Discussion In College Classroomsmentioning
confidence: 99%
See 3 more Smart Citations